A Randomized Trial of Prophylactic Antibiotics for Miscarriage Surgery. Issue 3 (September 2019) - Lissauer, D.; Wilson, A.; Hewitt, C.A.; Middleton, L.; Bishop, J.R.B.; Daniels, J.; Merriel, A.; Weeks, A.; Mhango, C.; Mataya, R.; Taulo, F.; Ngalawesa, T.; et al.
Abstract : ( N Engl J Med . 2019;380:1012–1021) It is unclear whether or not antibiotic prophylaxis prior to surgery to complete spontaneous abortion (removal of retained products of conception) can reduce postoperative pelvic infection. Evidence is lacking and international guidelines regarding this issue are also inconsistent. This issue is particularly concerning for women in low-income and middle-income countries, where rates of surgery for incomplete spontaneous abortion are high, and where pelvic infection can lead to serious illness and death. In order to help clarify this issue, the authors of the present study assessed the use of antibiotic prophylaxis (doxycycline and metronidazole, both inexpensive, heat-stable, and widely available) in women undergoing surgery to complete spontaneous abortion in low-resource settings.